ANALYSIS ON SCIENTIFIC STUDIES OF THE USE OF ANABOLIC STEROIDS IN BRAZIL: A STUDY OF REVIEW. (Fiep Bulletin - online, 2011)
This study aimed to analyze the scientific studies regarding the use of anabolic steroids in Brazil. The research design was a literature review using scientific articles and books, from January 1990 to September 2010 that focused on the use of anabolic androgenic steroids (AAS) in the country. The results show that there is little research on the EAA, mainly in the North and Midwest, and found no study in the Northeast. The profile of most users of AAS were young adults with age ranging from 18 to 29 years, bodybuilders, male, however the use of such substances is increasing among adolescents, and found no data to analyze specifically the use of AAS among women in our country. Since the main motivation for using AAS was to esthetics, however, among physical education teachers, other reasons prevailed as "personal marketing" and physical stress at work. With respect to the acquisition of AAS, the few findings show that most have access through pharmacy. It is concluded that more research is done on the prevalence of AAS use in males, teens, and especially among women in Brazil, identifying the profile, the motivation to use such substances and the form of access to AAS, as the misuse of AAS is becoming a public health problem.
Keywords: anabolic steroids; adults; Brazil